Characterizations of Effective Parameters and Circuit Modeling of U-Coupled Hybrid Ring Resonator Band Pass Filter - Atul Varshney; Duygu Nazan Gencoglan; Issa Elfergani; Jonathan Rodriguez; Chemseddine Zebiri; T. Mary Neebha (IEEE Access)
A two-port symmetrical, reciprocal, U-shaped mutually coupled hybrid ring resonator for ISM, L-band, and S-band applications is presented. The designed resonator is novel with a hybrid ring which comprises a square ring, a circular ring, and two U-shaped couplers for effective mutual coupling between rings and microstrip feeds. The proposed resonator serves as a bandpass filter with a passband ranging from 1.31 GHz to 2.68 GHz. This design offers superior performance compared to conventional ring resonators. The equivalent circuit model of the hybrid ring resonator validated the behavior of the filtering action. The resonator is validated using the measurement of reflection and transmission coefficients. The comparisons of measured values of the prototyped resonator model with CST-designed and HFSS-designed simulated values are found in good agreement in terms of design frequency 2.45 GHz, reflection and transmission coefficient values, and −10 dB bandwidth values. The equivalent circuit model is validated using ADS software. The designed circuit parameter values are found to be in excellent match with manually evaluated circuit parameters with tolerances under ±20%. Selectivity of the ring resonator is investigated for applicability of proposed resonator filter for practical applications. The hybrid resonator is good for the measurement of dielectric permittivity and loss tangent estimations at any frequency without the need for a calculator. The effective parameters are evaluated for characterizations of dielectric properties and their behavior as metamaterials. These attributes make the proposed hybrid ring resonator a highly versatile and efficient solution for next generation communication devices and applications.